2003
DOI: 10.1038/sj.bmt.1704228
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hematopoietic growth factors on the risk of graft-vs-host disease after allogeneic hematopoietic stem cell transplantation: a meta-analysis

Abstract: Summary:The effect of hematopoietic growth factors on neutrophil recovery after allogeneic transplantation is well-recognized. Recent laboratory studies demonstrated that these cytokines may also modify T-cell and dendritic cell function, but whether the effect is strong enough to alter the risk of GVHD is unclear. We performed a metaanalysis to determine the effect of G-CSF or GM-CSF on the risk of nonhematopoietic outcomes after allogeneic transplantation. A search of the literature from 1986 to present yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 24 publications
4
33
2
Order By: Relevance
“…In addition, there was no significant difference in chronic GVHD between patients who received G-CSF vs those who did not. 62 A meta-analysis by Ho et al 59 did not find an increase in the incidence of GVHD with the use of G-CSF. This meta-analysis had a total of 1198 patients with the majority (88%) undergoing BMT.…”
Section: Review Of Literature: Allogeneic Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there was no significant difference in chronic GVHD between patients who received G-CSF vs those who did not. 62 A meta-analysis by Ho et al 59 did not find an increase in the incidence of GVHD with the use of G-CSF. This meta-analysis had a total of 1198 patients with the majority (88%) undergoing BMT.…”
Section: Review Of Literature: Allogeneic Transplantationmentioning
confidence: 99%
“…Several studies have analyzed the efficacy of using G-CSF compared with control to decrease the number of neutropenic days after allogeneic transplantation in patients receiving either peripheral blood or BM cells. 12,13,[55][56][57][58][59][60][61][62] The outcomes from these studies are summarized in Table 5. Most of these studies included patients with hematological malignancies, whereas some also enrolled patients with solid tumors.…”
Section: Review Of Literature: Allogeneic Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, there have been conflicting reports of whether the use of growth factors increases the incidence of acute and chronic GvHD. 19,20 Although the incidence of grade II-IV acute GvHD has been similar for patients receiving allogeneic PBSC when compared with those receiving bone marrow, the incidence of chronic GvHD has been higher in PBSC recipients.…”
Section: Use Of Csfs During Allogeneic Transplantationmentioning
confidence: 99%
“…Thus, it was concluded that the use of hematopoietic growth factors after allo-SCT did not induce a significant change in the risk of acute or chronic GVHD, when these factors were used to shorten the initial period of neutropenia. 48 Obviously, such study has the strength of the large number of patients included, and the quality of a meta-analysis methodology, that is admitted to allow a relatively good standard of confidence level. In contradiction with the results of this meta-analysis, Remberger et al from a single center study suggested that G-CSF given after allo-SCT using HLAidentical sibling donors increases the risk of grade II-IV acute GVHD.…”
Section: G-csf and The Risk Of Gvhd After Allo-sctmentioning
confidence: 99%